Burden of atrial fibrillation in Māori and Pacific people in New Zealand: a cohort study. Issue 3 (6th March 2018) - Gu, Yulong; Doughty, Robert N.; Freedman, Ben; Kennelly, John; Warren, Jim; Harwood, Matire; Hulme, Richard; Paltridge, Chris; Teh, Ruth; Rolleston, Anna; Walker, Natalie
Abstract: Background: Atrial fibrillation (AF) is a major risk factor for ischaemic stroke and cardiovascular events. In New Zealand (NZ), Māori (indigenous New Zealanders) and Pacific people experience higher rates of AF compared with non‐Māori/non‐Pacific people. Aim: To describe a primary care population with AF in NZ. Stroke risk and medication adherence according to ethnicity are also detailed. Methods: Electronic medical records for adults (≥20 years, n = 135 840, including 19 918 Māori and 43 634 Pacific people) enrolled at 37 NZ general practices were analysed for AF diagnosis and associated medication prescription information. Results: The overall prevalence of non‐valvular AF (NVAF) in this population was 1.3% (1769), and increased with age (4.4% in people ≥55 years). Māori aged ≥55 years were more likely to be diagnosed with NVAF (7.3%) than Pacific (4.0%) and non‐Māori/non‐Pacific people (4.1%, P < 0.001). Māori and Pacific NVAF patients were diagnosed with AF 10 years earlier than non‐Māori/non‐Pacific patients (median age of diagnosis: Māori = 60 years, Pacific = 61 years, non‐Māori/non‐Pacific = 71 years, P < 0.001). Overall, 67% of NVAF patients were at high risk for stroke (CHA2 DS2 ‐VASc ≥ 2) at the time of AF diagnosis. Almost half (48%) of Māori and Pacific NVAF patients aged <65 years were at high risk for stroke, compared with 22% of non‐Māori/non‐Pacific ( P < 0.001). Irrespective of ethnic group, adherence to AF medication was suboptimal in those NVAF patients with a high risk of stroke or with stroke history. Conclusion: AF screening and stroke thromboprophylaxis in Māori and Pacific people could start below the age of 65 years in NZ.